Prevalence of tibial plateau fractures in patients from a public hospital in the Brazilian Amazon region - Lopes, Thiago Vaz (2022)
Accelerated urbanization, driver fatigue, disrespect for signs, speeding, abuse of alcoholic beverages and other illicit drugs in developing countries are the main causes that contribute to the increase in traffic accidents. The objective was to analyze the profile of victims with fracture of the tibial plateau and the prevalence of this pathology in care without an urgency and emergency hospital in Porto Velho/RO. This is a descriptive, cross-sectional study with retrospective data collection, carried out in December of the year 2021, having as a reference the visits from January to June of the same year, carried out by the orthopedics and traumatology sector, of a prompt service. Among the injured, 40 cases were related to fracture of the tibial plateau, 1.96% (40/2,043), and the distribution of these in the months of; January 15% (6/40), February 20% (8/40), March 10% (4/40); April 15% (6/40), May 22.5% (9/40) and June 17.5% (7/40). Among the different types of fractures, those of the tibial plateau constitute about 1% of all of them (SBOTCBR, 2007), however in this study we obtained 1.96%, practically double the value mentioned by this author. It is concluded that the profile of victims with tibial plateau fractures is predominantly male, adult, with motorcycle accidents as the main trauma mechanism.